MyD88 as a therapeutic target for inflammatory lung diseases. (4th May 2018) - Di Padova, Franco; Quesniaux, Valerie F. J.; Ryffel, Bernhard
ABSTRACT: Introduction : Myeloid differentiation primary response protein 88 (MyD88) is a critical adaptor protein involved in Toll-like and IL-1 receptor family signaling controlling innate immune responses and inflammation. Genetic deletion of MyD88 function results in profound suppression of inflammation and reduced resistance of the host to pathogens indicating non-redundant roles of MyD88. The TIR domain is critical for MyD88 dimerization and signaling for TLR and IL-1R family receptor. Areas covered : Emerging evidence suggests that chemical disruption of the TIR domain attenuates cell activation and inhibits in vivo MyD88-dependent inflammation. We review the development of MyD88 dimerization disruptors as a novel therapeutic approach of respiratory diseases with a focus on COPD. Expert opinion : There is a proof of concept that therapeutic targeting of MyD88 is feasible and first preclinical data are highly promising. This opens a great opportunity to treat exacerbations of COPD and other chronic respiratory diseases. However, extensive preclinical investigations and risk analyses are required with carefully evaluation of reduced host resistance and opportunistic infections.